2020
DOI: 10.1101/2020.04.29.069575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Stroke Induces Chronic Gut Dysbiosis and Neuroinflammation in Male Mice

Abstract: Recent literature implicates gut epithelia mucosa and intestinal microbiota as important players in post-stroke morbidity and mortality. As most studies have focused on the acute effects of stroke on gut dysbiosis, our study objective was to measure chronic, longitudinal changes in the gut microbiota and intestinal pathology following ischemic stroke. We hypothesized that mice with experimental ischemic stroke would exhibit chronic gut dysbiosis and intestinal pathology up to 36 days post-stroke compared to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…Our data also showed that the aged group had a higher Firmicutes/Bacteroidetes ratio (F/B ratio) as expected (Figure 1C), which is in support of inflamm-aging. Interestingly, aged GHS-R KO mice showed a significantly increased F/B ratio, which is in line with the microbiome profiles observed in diseases such as obesity, hypertension, and stroke [46][47][48]. Higher F/B ratio in the microbiota of aged GHS-R KO suggests that GHS-R ablation modifies the microbiota toward a disease-susceptible state.…”
Section: Discussionsupporting
confidence: 78%
“…Our data also showed that the aged group had a higher Firmicutes/Bacteroidetes ratio (F/B ratio) as expected (Figure 1C), which is in support of inflamm-aging. Interestingly, aged GHS-R KO mice showed a significantly increased F/B ratio, which is in line with the microbiome profiles observed in diseases such as obesity, hypertension, and stroke [46][47][48]. Higher F/B ratio in the microbiota of aged GHS-R KO suggests that GHS-R ablation modifies the microbiota toward a disease-susceptible state.…”
Section: Discussionsupporting
confidence: 78%
“…Compared with the PTS_TDW group, lactulose supplementation decreased the abundance of proinflammatory taxa (Gao et al, 2018;Ma et al, 2018) such as Desulfovibrio, Helicobacter, and Turicibacter, which might partially explain the decrease in a-diversity after drug administration [The relative abundance genus csv file and the heatmap of clustering for genus abundance and are in Supplemental Material and Supplemental Figure 4)]. In addition, the ratio of Firmicutes to Bacteroidetes, which is seen as a marker of dysbiosis in some studies, was decreased in the PTS_TDW group compared with the HC group (the average F/B ratios of the HC, PTS_TDW and PTS_LAC groups were 1.186,0.331 and 0.460 respectively; the relative abundance phylum csv file and the heatmap of clustering for phylum abundance are shown in the Supplemental Material and Supplemental Figure 5), while another study found that the Firmicutes to Bacteroidetes ratio increased after stroke (Brichacek et al, 2020); therefore, we speculated that an altered Firmicutes to Bacteroidetes ratio indicated gut dysbiosis.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in gastrointestinal function and commensal microbiota composition following stroke are well described both in patients (Cui et al, 2023; Xia et al, 2019; Xu et al, 2019; Yamashiro et al, 2017; Yin et al, 2015) and animal models (Benakis et al, 2016; Brichacek et al, 2020; Houlden et al, 2016; Singh et al, 2016; Stanley et al, 2016; Stanley et al, 2018). Importantly, changes in microbial communities correlate with worsened stroke outcome and secondary complications (Benakis et al, 2016; Brichacek et al, 2020; Singh et al, 2016; Stanley et al, 2016; Tuz et al, 2022; Xia et al, 2019). Indeed, antibiotic intervention post-stroke can lead to improved outcomes (Benakis et al, 2020b; Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that stroke also results in rapid changes in the composition of the gastrointestinal microbiota in both mice and humans (Houlden et al, 2016;Singh et al, 2016;Stanley et al, 2018), which is associated with increased mortality and worsened neurological function (Sun et al, 2021;Xia et al, 2019;. In experimental models of stroke in rodents, changes to the commensal microbiota are also associated with alterations in intestinal motility and loss of barrier integrity (Benakis and Liesz, 2022;Benakis et al, 2020a;Brichacek et al, 2020;Crapser et al, 2016;Delgado Jimenez and Benakis, 2021;Diaz-Marugan et al, 2023;Durgan et al, 2019;Houlden et al, 2016;Singh et al, 2016;Stanley et al, 2016;Stanley et al, 2018). Despite these observations, the underlying factors that drive loss of intestinal function and modulation of the microbiota following stroke remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%